Study on the Properties and Mechanisms of a Cement-Stabilized Aggregate Mixture With Vibration Mixing - Li, Ping; Wei, Di; Zhang, Dongmei; Xiong, Jianping; Xu, Sheng (Frontiers in Materials, 2021)
In order to master the influence of vibration mixing method on the performance of cement-stabilized aggregate mixture (CSAM), unconfined compressive strength test, drying shrinkage test and the influence of gradation characteristics on compressive strength were used to systematically analyzes the performance of CSAM based on vibration mixing in this paper. At the same time, the influence mechanism of vibration mixing on the interface transition zone of cement aggregate was analyzed by scanning electron microscope (SEM), and the influence of mixing method on cement dispersion uniformity was studied by Ethylene Diamine Tetraacetic Acid (EDTA) titration method. The results show that the 7d unconfined compressive strength and crack resistance of the CSAM with vibration mixing are better than those of the ordinary mixing, and the aggregate grade has a great influence on the compressive strength of the CSAM. Vibration mixing can improve the micro-water-cement ratio uniformity of CSAM, and significantly improve the bonding condition of the interface transition zone between cement paste and aggregate, thus enhancing the structural compactness of CSAM. The dispersion uniformity of cement under the vibration mixing is better than that of the ordinary mixing.